2021
DOI: 10.3390/diagnostics11071201
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila—Epidemiology and Characterization of Clinical Isolates, Slovenia, 2006–2020

Abstract: Legionella pneumophila is the causative agent of severe Legionnaires’ disease (LD). Although an increasing number of LD cases have been observed, published data from Slovenia are very limited and data on molecular epidemiology are even scarcer. The present retrospective study (2006–2020) reports the results of the microbiological diagnosis of LD, as well as the epidemiology and characterization of the Legionella clinical isolates. We tested urine samples from 15,540 patients with pneumonia symptoms for L. pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…L. pneumophila IgG seropositivity occurred in 37.5% of the sample population. Similar to the C. pneumoniae results, L. pneumophila IgG sero-detection revealed predominant positivity among men, which aligns with recent observations [ 27 ]. In addition, in each age group, one-third of the participants showed IgG positivity with L. pneumophila and there was no significant difference in IgG seropositivity distribution between different age groups ( Figure 2 C).…”
Section: Discussionsupporting
confidence: 91%
“…L. pneumophila IgG seropositivity occurred in 37.5% of the sample population. Similar to the C. pneumoniae results, L. pneumophila IgG sero-detection revealed predominant positivity among men, which aligns with recent observations [ 27 ]. In addition, in each age group, one-third of the participants showed IgG positivity with L. pneumophila and there was no significant difference in IgG seropositivity distribution between different age groups ( Figure 2 C).…”
Section: Discussionsupporting
confidence: 91%
“…Our study represents SBT analysis of 79 environmental L. pneumophila isolates obtained from municipal water at Latvian hotels, resulting in the identification of 21 different sequence types (ST), including three new STs. Previous studies have also described a high diversity of STs; for example, 27 different STs were identified in 78 isolates from Israel [ 26 ], 88 L. pneumophila isolates were divided into 33 STs in a study from Slovenia [ 31 ], while researchers from Canada reported that 141 sporadic cases of Legionnaires’ disease belonged to 57 different STs [ 32 ]. All these studies also identified new STs.…”
Section: Discussionmentioning
confidence: 99%
“…While the positive test prevalence of Legionella UAT is low (1.5–4.6%), efficiency of testing could be improved by focusing on patients with risk factors for Legionnaire’s disease. 69 , 84 , 85 One large retrospective study showed that patients with known risk factors (eg, hyponatremia, diarrhea, smoking) were tested only slightly more often than those without. 69 Additionally, even though Legionella species are known to thrive in warm, humid summer months, testing patterns did not vary by season.…”
Section: Urinary Antigen Test For the Diagnosis Of Legionel...mentioning
confidence: 99%